“African Agency” in Constructing “African Agency”: International Studies in Africa - D. А. Degterev (Международная аналитика, 2024)
This article is devoted to the problems and prospects for the development of international relations science in Tropical Africa. The study examines the phenomenon of African agency (subjectivity) at two levels: foreign policy expertise and practice, with a special emphasis on the first level. African agency is a conceptualization of the continent’s dependent development in the context of the agent-structural problem in international relations, which allows, through a constructivist approach, to more realistically convey the main features of international relations on the continent.The article presents the instrumental and even manipulative aspect of the “African agency” narrative, with special attention paid to the limits of agency. Among them is the insuﬃcient level of distribution of high-quality secondary and higher education, especially in national languages.The Soviet experience of Mali’s social science emerging from the “intellectual cocoon” of the former metropolis is shown. The problem of financing leading African think tanks on international relations, including their dependence on Western and Chinese sources, as well as the increasing hierarchy of international relations science, which negatively aﬀects the state of aﬀairs on the continent.An analysis of the participation of African researchers in international conferences, including within the framework of the International Studies Association (ISA), is conducted. Much attention is paid to positive examples of the development of African agency, e.g. five International Congresses of Africanists in the 1960–1980s, as well as the activities of the Council for the Development of Social Science Research in Africa (CODESRIA). The main elements of the successful development of CODESRIA in the 1970–1980s are presented. Conclusions are made on the prospects for strengthening agency in international studies of Africa in the context of modern geopolitical transformations.